2010
DOI: 10.2353/ajpath.2010.090937
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and Axonal Loss Are Selectively Linked to Fibrillar Amyloid-β within Plaques of the Aged Primate Cerebral Cortex

Abstract: The amyloid-␤ peptide (A␤) deposited in plaques in Alzheimer's disease has been shown to cause degeneration of neurons in experimental paradigms in vivo and in vitro. However, it has been difficult to convincingly demonstrate toxicity of native amyloid deposits in the aged and Alzheimer brains. Here we provide evidence that the fibrillar conformation of A␤ (fA␤) deposited in compact plaques is associated with the pathologies observed in Alzheimer brains. fA␤ containing compact but not diffuse plaques in the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 61 publications
1
32
0
1
Order By: Relevance
“…Aβ levels accumulate with age, reaching similar levels in the cortex to that observed in human AD, and there is often more Aβ42 than Aβ40 [126]. Plaques are typically found in rhesus monkeys that are older than 25 years and they have a similar distribution that that observed in humans; more being present in the cortex than the hippocampus [54, 56, 96, 134, 146, 150, 164, 165]. In contrast to great apes, parenchymal plaques are more prevalent than CAA in rhesus monkeys, with CAA present in approximately one third of aged rhesus monkeys [164, 165].…”
Section: Physiological Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aβ levels accumulate with age, reaching similar levels in the cortex to that observed in human AD, and there is often more Aβ42 than Aβ40 [126]. Plaques are typically found in rhesus monkeys that are older than 25 years and they have a similar distribution that that observed in humans; more being present in the cortex than the hippocampus [54, 56, 96, 134, 146, 150, 164, 165]. In contrast to great apes, parenchymal plaques are more prevalent than CAA in rhesus monkeys, with CAA present in approximately one third of aged rhesus monkeys [164, 165].…”
Section: Physiological Modelsmentioning
confidence: 99%
“…In contrast to great apes, parenchymal plaques are more prevalent than CAA in rhesus monkeys, with CAA present in approximately one third of aged rhesus monkeys [164, 165]. The majority of plaques are diffuse; only approximately 20% contained fibrillar Aβ [134, 146]. Minor neuronal loss is observed immediately around compact plaques; however, there is no evidence of widespread neuronal loss, even in brain regions with a high plaque load [146].…”
Section: Physiological Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence further indicates that the fibrillar conformation of Aβ deposited in compact plaques is associated with the pathologies observed in AD. Quantitative analysis revealed that the area adjacent to fibrillar Aβ, containing compact but not diffuse plaques in aged rhesus, aged human, and AD cortex, displays significant loss of neurons and small but statistically significant reduction in the density of cholinergic axons [51]. …”
Section: Amyloid Beta Particularly Aβ42 In Alzheimer's Diseasementioning
confidence: 99%
“…Also, the signal transduction pathways of tau hyperphosphorylation may be related to accumulated Aβ [74-77]. Fibrillar Aβ containing compact but not diffuse plaques in the aged rhesus cortex also contained activated microglia and clusters of phosphorylated tau-positive swollen neuritis [51]. On the other hand, recent study showed that peptides from structure-based designs can disrupt the Aβ fibril formation of original proteins, including those, such as tau protein, that lack fully ordered native structures.…”
Section: Amyloid Beta Particularly Aβ42 In Alzheimer's Diseasementioning
confidence: 99%